The Dismounting Horseman Scene on Cilician Coins - Veselý, Petr (KOINON: The International Journal of Classical Numismatic Studies, 2023)
Several cities in Cilicia minted coins in the pre-Hellenistic period that show a horseman dismounting from a horse. Most of these issues can be safely attributed to Kelenderis and Holmoi in Cilicia Trachea, and one rare issue probably comes from Issos in Cilicia Pedias. However, there is also another rare issue remotely resembling Kelenderis coins, which cannot be assigned to any of these mints, nor can it be described as a mere imitation. The issue of this unknown mint differs from the coins of Kelenderis, among other things, in that the rider holds a cutlass, and significantly different additional symbols are used on the reverse. In addition, a specimen of another coin type resembling Kelenderis coins has appeared on the market, which cannot be assigned to any of the mints mentioned. Thus, there were probably as many as five mints in Cilicia or adjacent areas of the eastern Mediterranean that struck coins with the dismounting horseman scene. This scene is specific to the Greek equestrian competition called the kalpe, which was closely related to military equestrian training. Depictions of similar agonistic scenes with both unarmed and armed horsemen can also be found on coins minted in the Classical and early Hellenistic periods in Calabria and Sicily and possibly also in Ionia. It is suggested that the main reason for minting these coins was to present the horsemanship of local horsemen and their readiness for military tasks.